Safety Assessment of Speed Governing Systems in Hydroelectric Power Plants: A Functional Safety Perspective - Nezihe Merve Balcı; Özgür Turay Kaymakçı (Journal of Advanced Research in Natural and Applied Sciences)
In line with the advancing technology, reliability has become one of the critical factors to be taken into consideration by the operators in the energy sector to minimize losses regarding cost and time. This issue is directly related to the reliability of the elements, namely the subsystems that make up the system. This study examines the control architecture of speed governing system within the turbine control system of hydroelectric power plants, which has to be regarded as a critical system and provides an indispensable source of guidance and knowledge to researchers and also implementation engineers as well. For this perspective, a reliability analysis has been performed for the speed governing system and the risks with the control system have been revealed. Taking IEC 61508 and IEC 61511 standards as reference within this scope, the safety concepts and the related parameters have been explained and the corresponding methods for risk analysis have been mentioned. As a result, a new safety-related control system configuration overcoming the unacceptable risks with the speed governing system has also been proposed. It has been proved that safety integrity level of the proposed safety-related control system is at the desired level that can make the related safety related functions verify the identified safety level.